The proem of Aristotle’s Metaphysics: an interpretation of Metaph. A1 - Cecílio, Guilherme da Costa Assunção (Revista Archai, 2018)
Based on the notion of proem as exposed in Aristotle’s Rhetoric, we examine in detail Metaph. A1. Our goal is to understand the argument contained in this chapter, as we also endeavour to show how the Stagirite introduces with uttermost caution the theme of wisdom [ÏƒÎ¿Ï†Î¯Î±], that which is the incarnation of the preeminent science in the first book of the Metaphysics. The attention we devote to the proem of this work is explained by the importance we attribute, unlike much of contemporary scholars, to ÏƒÎ¿Ï†Î¯Î±, that is, the science of first causes and principles, which we consider to be, ultimately, the pivotal formulation of the supreme science in the Metaphysics.